Deverbal nominalizations without overt suffixation in French - Sleeman, Petra (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
Recent work on argument taking deverbal zero nouns in English has shown that they are more present in that language than was previously thought. In this paper the presence and productivity of argument taking zero-derived nouns in French is investigated. It is shown that to determine which nouns can count as zero nouns, several decisions have to be made. This concerns their gender (do both masculine and feminine nouns have to be included in the research?), the determination of what counts as an argument, the criteria used to determine if a noun is an argument taking noun, the form and category that the base may have. On the basis of the adopted criteria and a dictionary and database research, a corpus of French zero-derived nouns in French is composed and analyzed. The results show that, as in English, zero-derived nouns in French are more productive than was thought.